Polymorphisms in the IL17A gene are not involved in the development of preeclampsia in the Brazilian population - Sarah Cristina S. V. Tanaka; Andrezza Cristina C. Hortolani; Cristina W. Pissetti; Marina C. Paschoini; Mariangela T. Cintra-Ruiz; Virmondes Rodrigues Jr; Marly Aparecida S. Balarin (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Introduction: Preeclampsia is defined by the development of hypertension associated with proteinuria after the 20th week of gestation in previously normotensive women. IL17A is a potent inducer of tissue inflammation and polymorphisms in the IL17A gene can modulate gene expression and affect the functioning of Th17 cells, strengthening susceptibility to preeclampsia. Objective: To investigate the polymorphisms rs4711998 A>G, rs8193036 C>T and rs2275913 A>G in the IL17A gene in women with preeclampsia. Methods: This is a control case study, composed of 263 women, 89 with preeclampsia and 174 of the control group. The polymorphisms investigated by real time polymerase chain reaction (PCR) allele discrimination technique. The risk of IL17A polymorphisms contributing to preeclampsia was assessed by the inheritance model through logistic regression. Statistical power presented 99.5% for association detection. Statistical significance was defined as p < 0.05. Results: Genotype frequencies as well as multiple logistic regression analysis were not statistically significant for the rs4711998 A>G, rs8193036 C>T and rs2275913 A>G polymorphisms of the IL17A gene. No association was found between any haplotypes of the polymorphisms investigated and the risk of developing PE. Conclusion: There is no association between the allele frequencies, genotype, inheritance models and haplotypes of the rs4711998 A>G, rs8193036 C>T and rs2275913 A>G polymorphisms of the IL17A gene and PE.